New Age in the Geological Evolution of the Cerro de Mercado Iron Oxide Apatite Deposit, Mexico: Implication in the Durango Apatite Standard (Dap) Age Variability - Henriquez-Barrientos, F (Elsevier Ltd, 2018)
Cerro de Mercado Iron Oxide Apatite deposit (CM-IOA) is known as a classical example of an IOA deposit worldwide and is also probably the most prolific locality in terms of gem-quality fluorapatite. The CM-IOA deposit is located in the Chupaderos Caldera Complex (CCC), a large rhyolitic volcanic center belonging to the Upper Volcanic Supergroup of Oligocene age. The main Cerro de Mercado IOA mineralization body is crosscut by a kilometer long rhyodacite dyke that acted as channelway for the rhyodacite flow. The rhyodacite dyke crosscuts all the volcanic sequence. K-Ar ages of this dyke range from ca. 28 to 27 Ma. Apatite in the Cerro de Mercado deposit appears in two different positions, (1) altered crystals intergrown with martite within massive mineralization, with or without diopside; and (2) on martite in degassing cavities and fracture zones, with accompanying chalcedony and calcite. Crystallization of the apatite phase was complete prior to the eruption of the overlying felsic flows of the Tinaja Member of the Cacaria Formation at ca. 31.44 Ma and preserve of potential late thermal event (McDowell et al., 2005). The mean ages reported by numerous and different isotopic methods for the fluorapatite DAP are coincident within the margins of uncertainty with the volcanic host rocks ages. But DAP ages reported present a significant variability of up to 8%. Such variability is also found in all dating technics applied in Durango Apatite (fission-track, U/Pb and (U-Th)/He ages) and suggest a thermal resetting related to the late volcanic event at 28-27 Ma. © 2018